FACTORS INFLUENCING CONSUMPTION PATTERN OF ICE CREAM IN BENGALURU MARKET - Sivaram, Muniandy (Indian Journal of Dairy Science, 2015)
Ice cream is the most popular dairy product of the 21st century. It is a frozen dessert, usually consumed after food. To know the consumption pattern of ice cream in Bengaluru urban district of Karnataka State, India, the data from three hundred sample respondents was collected using multistage stratified random sampling technique. The study revealed that the per capita expenditure on ice cream was found to be Rs.99 which contributed about 5.40 per cent of the total monthly per capita food expenditure. The variables which had significant correlation with monthly per capita expenditure on consumption of ice cream were type of family, family size, annual family income, food habit and monthly expenditure on non-food items. Among the various flavours of ice cream, majority of the consumers preferred vanilla (43.9%) flavour followed by butter scotch (34.6%) and chocolate (33.9%) flavours. The study portrayed that majority (42.9%) of the consumers preferred Amul brand of ice cream followed by Arun (16.1%) brand. Logistic regression analysis revealed that the preference for Amul brand increased significantly with the age of the respondents and family expenditure on food items. The consumers preferred different brands of ice cream because of its taste, good quality and flavour.Â